2010
DOI: 10.1038/ja.2010.98
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure elucidation of a novel androgen antagonist, arabilin, produced by Streptomyces sp. MK756-CF1

Abstract: In the course of screening for a new type of androgen receptor (AR) antagonist, we isolated a novel compound, arabilin, with two structural isomers, spectinabilin and SNF4435C, produced by Streptomyces sp. MK756-CF1. Structure elucidation on the basis of the spectroscopic properties showed that arabilin is a novel polypropionate-derived metabolite with a p-nitrophenyl group and a substituted c-pyrone ring. Arabilin competitively blocked the binding of androgen to the ligand-binding domain of AR in vitro. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Compounds 1 , 2 , and 10 were proved to be known compounds of flavofungins I ( 1 ) and II ( 2 ) 30, 31 and spectinabilin ( 10 ) 3234 based on their HRESIMS and NMR data (Tables 1 and 2) as well as a comparison to the data of references. Flavofungins I ( 1 ) and II ( 2 ) were 32-membered polyene-polyol macrolides with a conjugated chain of five unsubstituted double bonds connected to a polyol fragment with eight hydroxy groups alternated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 1 , 2 , and 10 were proved to be known compounds of flavofungins I ( 1 ) and II ( 2 ) 30, 31 and spectinabilin ( 10 ) 3234 based on their HRESIMS and NMR data (Tables 1 and 2) as well as a comparison to the data of references. Flavofungins I ( 1 ) and II ( 2 ) were 32-membered polyene-polyol macrolides with a conjugated chain of five unsubstituted double bonds connected to a polyol fragment with eight hydroxy groups alternated.…”
Section: Resultsmentioning
confidence: 99%
“…Flavofungins I ( 1 ) and II ( 2 ) were 32-membered polyene-polyol macrolides with a conjugated chain of five unsubstituted double bonds connected to a polyol fragment with eight hydroxy groups alternated. Both flavofungins I ( 1 ) and II ( 2 ) were reported to have antifungal and antiviral activities 19 , while spectinabilin ( 10 ) was a nitro-substituted polyketide with activity to block the binding of androgen to the ligand-binding domain of androgen receptor 34 .…”
Section: Resultsmentioning
confidence: 99%
“…A B * * * * overexpression and being hypersensitive to low levels of androgens in vitro. Subsequent screening of other thiohydantoin derivatives revealed that CH5137291 exhibited antitumor activity in CRPC xenografts where CH4933468 failed to prevent their growth [78].…”
Section: Thiohydantoin Derivativesmentioning
confidence: 99%
“…MK756-CF1, the new polypropionate derivative, arabilin Fig. (2), was proved to be a competitive ligand of AR, showing an inhibitory activity on the androgen-induced prostate-specific antigen mRNA expression in prostate cancer LNCaP cells [86].…”
Section: Natural Androgen Receptor (Ar) Ligandsmentioning
confidence: 99%